Self-stigma in PTSD: Prevalence and correlates. (July 2018) - Bonfils, Kelsey A.; Lysaker, Paul H.; Yanos, Philip T.; Siegel, Alysia; Leonhardt, Bethany L.; James, Alison V.; Brustuen, Beth; Luedtke, Brandi; Davis, Louanne W.
Highlights: Self-stigma is the internalization of negative stereotypes about mental illnesses. We know much about self-stigma in schizophrenia, but little about its presence in PTSD. We compared a PTSD sample ( n  = 46) to a schizophrenia sample ( n  = 82) on self-stigma. Results suggest a significant level of self-stigma exists among veterans with PTSD. Self-stigma had an effect on PTSD and commonly comorbid symptoms, like depression. Abstract: Self-stigma is the internalization of negative societal stereotypes about those with mental illnesses. While self-stigma has been carefully characterized in severe mental disorders, like schizophrenia, the field has yet to examine the prevalence and correlates of self-stigma in post-traumatic stress disorder (PTSD). Thus, we assessed self-stigma in veterans diagnosed with PTSD and compared with veterans with schizophrenia. We further examined associations between PTSD, depressive symptoms and self-stigma in the PTSD sample. Data came from two larger studies of people with PTSD ( n  = 46) and schizophrenia-spectrum disorders ( n  = 82). All participants completed the Internalized Stigma of Mental Illness Scale (ISMIS). Results revealed that people with schizophrenia report more experiences of discrimination as a result of stigma than do those with PTSD, but these diagnostic groups did not differ for other subscales. In the PTSD group, feelings of alienation positively correlated with PTSD and depressive symptoms; other subscales positively correlated with depressive symptoms only. Taken together, results suggest a significant level of self-stigma exists among veterans with PTSD, and that self-stigma has an effect on PTSD and commonly comorbid symptoms, like depression. Future work should investigate whether current self-stigma interventions for other groups could be applicable for those with PTSD.